Anti-oxidant and anti-bacterial activities of 11 Calophyllum species from Indonesia - Jamilah Abbas (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2019)
Members of Calophyllum (Calophyllaceae) are commonly used as herbal medicine in Indonesia from the beginning of civilization. Due to their tremendous potential as a source for pharmaceutical industry, we selected 11 Calophyllum species for the current anti-oxidant and anti-bacterial studies, namely, Calophyllum euryphyllum, C. bicolor, C. flavoramulum, C incrassaptum, C. lowei, C. macrophyllum, C. nodosum, C. soulattri, C. tetrapterum, C. teysmannii, and C. tomentosum. The methods include Calophyllum stem bark extraction and separation into n-hexane, ethyl acetate, and butanol fractions, followed by the antioxidant analysis using DPPH (2,2-diphenyl-1-picrylhydrazyl radical scavenging) and the anti-bacterial activity against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Pseudomonas aeruginosa. The results showed that n-hexane fraction of C. soulattri exhibited the best anti-oxidant activity (IC50 = 2.2 µg/m). This study also showed that a xanthone compound isolated from C. macrophyllum, namely, 1,8 - dihydroxy-6 methoxy xanthone exhibited the anti-oxidant activity with IC50 = 1.56 ppm.